Putting UK DCTN studies into practice: a nurse and patient perspective of the investigator day for the BLISTER and STOP GAP trials - Westmoreland, Melanie; Teh-Burden, Esther; Layfield, Carron (British Dermatological Nursing Group, 2017)
The BLISTER and STOP GAP studies are two important trials in the field of dermatology and also for the UK Dermatology Clinical Trials Network (UK DCTN) as a collaborative network. They make a significant contribution to our limited evidence base for the management of bullous pemphigoid and pyoderma gangrenosum respectively. In keeping with the priorities of the UK DCTN, both trials investigated treatments routinely available in dermatology and focused on rarer skin diseases which benefited from involvement of the network to recruit a sufficient number of patients. The ‘Putting UK DCTN Studies into Practice Event’ was an opportunity for clinicians, patients and researchers involved to share their experiences of the studies and the related skin conditions. Investigators from both trials commented on their experiences and how being involved in the BLISTER and STOP GAP trials had affected their attitude to research and changed their clinical practice. In this article we hope to continue the ethos of a shared experience by providing an insight of the investigator day from a nursing and patient perspective.